PENGARUH PERAN KOMITE SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SDN 2 CILANGKAP - Nurhakim; Tutuk Ningsih (STKIP Subang, 2022)
The community has a strategic role in efforts to improve the quality of education in schools, which is reflected in the existence of a school committee as a representative of the parents to control the running of the school, these efforts are implemented through their participation and involvement both morally and materially. The role of society with educational institutions is a series of the entire process of implementing education that is planned and pursued deliberately and earnestly. Education has a central role in the nation's civilization in striving to increase human resources in a better direction. Education is expected to be able to then shape or produce a person in order to develop his attitudes, skills and intellectual awareness to become a skilled, intelligent, and noble human being. In this case, the role of education in Indonesia is not only from the students and school institutions, but the community also has an important role in developing education both acting as a source, implementer and user of educational outcomes. This is what the two parties have not fully realized, both of which consider that the two parties are an integral part. In order to realize the collaboration between the two parties, it is certainly necessary to function the field of public relations as a mediator for communication between educational institutions and the community. This research uses qualitative methods. The subject of his research was the people of kalisabuk village. The results showed that the role given by the community will provide a reference in the development of educational institutions both in terms of quality and quantity of education in Cilangkap village, Gumelar district, Banyumas regency.